Airborne contact allergy to methylisothiazolinone in a young atopic male. - Romita, P.; Foti, C.; Stingeni, L.; Angelini, G.; Bonamonte, D. (European Journal of Pediatric Dermatology, 2018)
Isothiazolinones are widely used as preservatives in skincare topical products, paints and household cleaning agents. Their contact sensitizing potential is well-known. Moreover, they can cause occupational contact allergy and airborne allergic contact dermatitis. A case of airborne contact allergy to methylisothiazolinone in a 5-year-old child was here reported.